Mathematics Learning Anxiety Among Senior High School Students: A Qualitative Case Study - Yuzarion Yuzarion; Yenti Arsini; Masyhuril Fajar; Yusutria Yusutria; Akhmad Fajar Prasetya; Rina Febriana (Kuras Institute, 2026)
Mathematics learning anxiety is a prevalent issue among high school students that can adversely affect academic performance and psychological well-being. Despite extensive quantitative research, little is known about the lived experiences and psychospiritual dimensions of students facing mathematics anxiety, particularly within Islamic educational settings. This qualitative case study explores the determinants of mathematics learning anxiety among students at Senior High School (SMA) Muhammadiyah Yogyakarta, Indonesia. Participants were purposively selected based on active enrollment, observable signs of mathematics anxiety, and willingness to provide informed consent. Data were collected through observation, semi-structured interviews, and document analysis, then analyzed thematically. Findings indicate that students experience psychosomatic symptoms, cognitive difficulties, altered learning behavior, and neurophysiological disturbances. Contributing factors include low self-efficacy, poor concentration, fear of failure, and the perception of mathematics as inherently difficult. Anxiety manifested during lessons and assessments, negatively influencing problem-solving, conceptual understanding, and overall academic achievement. This study highlights the need for holistic support strategies in schools that address both psychological and psychospiritual well-being, integrating educational and Islamic principles to reduce mathematics learning anxiety and enhance student outcomes.